Effects of dabigatran on the cellular and protein phase of coagulation in patients with coronary artery disease on dual antiplatelet therapy with aspirin and clopidogrel - Franchi, Francesco; Rollini, Fabiana; Cho, Jung Rae; King, Rhodri; Phoenix, Fladia; Bhatti, Mona; DeGroat, Christopher; Tello-Montoliu, Antonio; Zenni, Martin M.; Guzman, Luis A.; Bass, Theodore A.; Ajjan, Ramzi A.; Angiolillo, Dominick J. (Thrombosis and Haemostasis, 2016)
There is growing interest in understanding the effects of adding an oral anticoagulant in patients on dual antiplatelet therapy (DAPT). Vitamin K antagonists (VKAs) and clopidogrel represent the most broadly utilised oral anticoagulant and P2Y12 receptor inhibitor, respectively. However, VKAs can interfere with clopidogrel metabolism via the cytochrome P450 (CYP) system which in turn may result in an increase in platelet reactivity. Dabigatran is a direct acting (anti-II) oral anticoagulant which does not interfere with CYP and has favourable safety and efficacy profiles compared with VKAs. The pharmacodynamic (PD) effects on platelet reactivity and clot kinetic of adjunctive dabigatran therapy in patients on DAPT are poorly explored. In this prospective, randomised, double-blind, placebo-controlled PD study, patients (n=30) on maintenance DAPT with aspirin and clopidogrel were randomised to either dabigatran 150 mg bid or placebo for seven days. PD testing was performed before and after treatment using four different assays exploring multiple pathways of platelet aggregation and fibrin clot kinetics: light transmittance aggregometry (LTA), multiple electrode aggregometry (MEA), kaolin-activated thromboelastography (TEG) and turbidimetric assays. There were no differences in multiple measures of platelet reactivity investigating purinergic and non-purinergic signaling pathways assessed by LTA, MEA and TEG platelet mapping. Dabigatran significantly increased parameters related to thrombin activity and thrombus generation, and delayed fibrin clot formation, without affecting clot structure or fibrinolysis. In conclusion, in patients on DAPT with aspirin and clopidogrel, adjunctive dabigatran therapy is not associated with modulation of profiles of platelet reactivity as determined by several assays assessing multiple platelet signalling pathways. However, dabigatran significantly interferes with parameters related to thrombin activity and delays fibrin clot formation.
Keywords: Antithrombin; platelet pharmacology; pharmacodynamics; thrombosis